“Mutual Assistance” Culture to Maintain Corporate Sustainability - Karsam Karsam; Erfan Erfiansyah; Inugrah Ratia Pratiwi; Hendriyana Hendriyana; Siti Kodariah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This article aims to demonstrate that corporate sustainability will be more balanced and sustainable if it is based on the philosophy of